Mechanism of Filtration Behaviors of Cement-Based Grout in Saturated Sand under Different Grouting Conditions. (5th May 2022) - Xu, Shanlin; Cao, Hongtao; Zhu, Yanzhen; Sun, Honglei; Lu, Jingling; Shi, Junqiang
Abstract : Cement-based grout has been widely used in various civil engineering applications. However, the filtration behaviors of it when grouting the porous geological masses vary a lot under different grouting conditions, which significantly influences its penetration and the enhancement effect. The purpose of this work was to better understand the filtration of cement-based grout in porous sand by conducting a series of visualized laboratory tests and EDTA titration tests. The experimental results show that the cement filtration, including the penetration, retention, and formation of cement filter cake above the grouting body, is collectively influenced by different grouting factors. With the increase of the soil samples' pore size and the cement slurry's water-cement ratio, the penetrated distance and amount of cement in sand increase. However, the penetration does not increase monotonically with the grouting pressure. Too excessive grouting pressure (e.g., 300 kPa in this study) accelerates the formation of cement filter cake and thus stops the subsequent cement infiltration. The mechanisms of different filtration behaviors were explained from microscopic particle clogging in the pore throat of the porous media. Furthermore, the reduced permeability of the sand column with the retained cement due to filtration was discussed, and the dewatering phenomenon of the cement slurry after filter cake formation was first revealed.